Insights into the effects of transgenic glyphosate-resistant semiwild soybean on soil microbial diversity - Shijia Dong; Yunfei Gao; Liu Xin; Wei Ding (Scientific Reports)
Abstract Transgenic soybean [Glycine max(L.) Merrill] currently covers approximately 80% of the global crop area for this species, with the majority of transgenic plants being glyphosate resistant (Roundup Ready, GR or RR). However, there is significant concern regarding the potential effects of GM crops and their byproducts on soil microbial communities. During our research, we discovered a type of semiwild soybean that emerged due to genetic drift at a transgenic test site. Nevertheless, the ecological risk to soil rhizosphere microorganisms associated with planting semiwild soybean following genetic drift remains unclear. Therefore, we conducted a field experiment and collected soil samples at various stages of plant growth. Our results indicate that the species diversity of rhizosphere bacteria in transgenic glyphosate-resistant semiwild soybean was also not significantly different from that observed in other types of soybean. Additionally, Basidiomycota had beneficial effects on rhizosphere fungi during the flowering and maturation stages in transgenic glyphosate-tolerant semiwild soybean. These findings provide valuable insights into how genetic drift in transgenic soybean may impact the soil microenvironment.